Penguatan Peran Guru dalam Reformasi Manajemen Kurikulum di MA Darussalam: Solusi Berbasis Kepemimpinan - Muh. Imam Khaudli; Fitdarus Kussuma (STIKes Ibnu Sina Ajibarang, 2025)
This study highlights the importance of strengthening the role of teachers in curriculum management reform through a transformational leadership approach at MA Darussalam. The aim of the research is to conduct an in-depth analysis of strategies for empowering teachers within the context of curriculum reform, enabling them to become not only implementers but also designers and drivers of instructional change. A qualitative approach was employed, using a case study method to contextually understand the dynamics of leadership and teacher participation in curriculum management. Data collection techniques included in-depth interviews, participatory observation, and documentation, with purposive sampling of informants consisting of the school principal, the vice principal of curriculum affairs, and teachers from various subject areas. Data analysis was conducted thematically to identify patterns of roles, collaboration, and the influence of leadership on enhancing teacher participation. The findings reveal that participatory transformational leadership encourages active teacher involvement in curriculum development, enhances professional motivation, and fosters a learning ecosystem that is more adaptive and responsive to the socio-religious context of the madrasah. The study recommends the implementation of a leadership model based on collaboration and reflection as a sustainable and relevant strategy for curriculum reform in pesantren based madrasahs.